(untitled) (International Journal of Innovative Research in Engineering & Management, 2022)
This study is a consequence of dissatisfaction with the outcomes of recent educational changes. These attempts failed. They must be given up. In their place, we must acknowledge that economic disparity creates numerous societal issues, including educational issues. Sadly, among all affluent countries, the USA has the greatest economic disparity between rich and poor. There is a correlation between a country’s or state’s economic imbalance and the prevalence of social problems. As a result, better social and economic initiatives might have a greater impact on our schools than school curriculum alone. Teachers, curriculum, assessment and administration have all been targeted as potential causes of school failure. This article argues that America’s educational issues stem from factors outside of school, mainly economic disparity. Thus, focused economic and social policies may be more effective in improving schools than virtually any other federal, state, or municipal policy proposal. This article examines the causes behind virtually every recent school reform effort’s failure. It is a study on how inequality impacts our society as a whole, for example, research and social reforms that may improve our educational establishments. The greatest approach to improve American schools is to create employment that pay a decent wage. Other programmes for disadvantaged kids are mentioned. Inequality in income, and the poverty that results from it, is what matters most for education.